Integrasi Adat dan Syariat: Analisis Filosofis Pendidikan Islam dalam Perspektif Adat Basandi Syara’, Syara’ Basandi Kitabullah di Minangkabau - Joni Indra Wandi; Cipto Duwi Priyono; Reflianto; Nora Afnita; Farida Ariani (CV. Kalimasada Group, 2026)
This study analyzes the integration of custom (adat) and Islamic law (sharia) in Islamic education through the philosophical perspective of Adat Basandi Syara’, Syara’ Basandi Kitabullah (ABS-SBK) in Minangkabau. It examines the construction of ABS-SBK as the ontological, epistemological, and axiological foundation of Islamic education and its relevance to contemporary educational challenges. Using a qualitative library-research design with a systematic review procedure, the study draws on documented classical sources (tambo and petatah-petitih) and peer-reviewed publications from the last decade, screened through explicit inclusion and exclusion criteria. Data were analyzed through reduction, thematic categorization, and critical-hermeneutic interpretation, with source triangulation to ensure credibility. The findings show that ABS-SBK is an integrative paradigm harmonizing cultural values and Islamic principles into a holistic educational system, historically embodied in the surau. In modern education, however, its implementation faces secularization, fragmentation of knowledge, and the marginalization of local values in formal curricula. The study proposes a reconstruction model linking philosophical grounding, contextual curriculum, and the synergy of ninik mamak, alim ulama, and cadiak pandai. Its contribution lies in systematizing ABS-SBK into an explicit ontological-epistemological-axiological framework for value-based, contextual Islamic education.